STUDI PENGELOLAAN SUMBER DAYA ALAM DAN LINGKUNGAN BERBASIS KEARIFAN LOKAL MASYARAKAT: KASUS CAGAR ALAM PEGUNUNGAN ARFAK, KABUPATEN MANOKWARI PAPUA BARAT - , FIRAON ULLO, S.HUT.; , Prof. Dr.Ir.H. Djoko Marsono ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research was intended to identify biophysical condition, social economic condition and interaction type of local wisdom of Moile ethnic on natural resource management in Arfak mountain natural reserve. This exploration research is exâpost factor so its result can be used as reflection and input for future policy. Research subject is people of Moile ethnic living in Mokwam village Minyambow district of Manokwari regency, West Papua. Data was gathered with questionnaire, while other supporting data was obtained through observation, and interview. Data was analyzed using descriptive statistic and analytic network process (ANP). Natural reserve in Arfak Mountain locates in Bird Head area of Manokwari. It has hilliness and waving topography with highest peak of 2800 meter above sea level. Arfak mountain is 68,325 ha ranging from 010 00 â 01029 SL and 133053 â 1340EL. Moile ethnic and other ethnics such as Hatam, Sough and Meyakh are native ethnic that live in Arfak mountain from generation to generation since before it was determined as natural reserve. They live communally and have strong dependence on forest in meeting daily needs such as agriculture, hunting, collecting, and using wood. Moile ethnic people hold their custom they inherit from their ancestor in taking forest product. Their custom has wisdom in conservation that prohibits excessive forest exploitation. The principle is known as Ig ya ser hanjob, which means utilizing forest for live sustainability with still considering conservation. Government may play role in the local wisdom of Moile ethnic through Natural Resource Conservation Agency (BKSDA) and Local government. Government may optimize Moile ethnic wisdom in hunting, land cultivation, collecting and wood utilization. Then the area is kept together for more sustainable. In quality side, government can help by introducing better technique such as extension for planting to improve land cultivation, open animal husbandry to conserve habitat in general and hunted animal in particular, preservation technique for collection result and wood utilization. Human resource should be simultaneously improved, so Ig ya ser hanjob wisdom in utilizing forest can be transformed better.